LCC methodology application for equipment replacement strategy definition - Kayashima,Eduardo Cruvinel (2019)
Abstract Presented herein are the economic viability results when applying the analysis techniques for investments to replace mobile equipment. Due to the high cost involved in these exchanges, an economic model was designed based on Life Cycle Cost analysis and through the Equivalent Annual Uniform Cost method, evaluating and comparing the best option: to maintain or replace the equipment, and to define when is the best time for this replacement. This methodology, besides defining the best moment of replacement, is also applicable for defining the moment of the equipment purchases because this methodology allows cost annualization and consequently, it is possible to compare equipment with different life times. This means, they allow the choice of the best financial option for the company.